Knowledge And Attitudes Of Pharmacy Students Towards Pharmacogenomics Among Universities In Jordan And West Bank Of Palestine - Jarrar Y; Mosleh R; Hawash M; Jarrar Q (Dove Medical Press, 2019)
Yazun Jarrar,1 Rami Mosleh,2 Mohammed Hawash,2 Qais Jarrar3 1Department of Pharmacy, College of Pharmacy, Al-Zaytoonah University of Jordan, Amman, Jordan; 2Department of Pharmacy, Faculty of Medicine and Health Sciences, An-Najah National University, Nablus 00970, Palestine; 3Department of Pharmaceutical Science, Al-Isra’a University, Amman, JordanCorrespondence: Yazun JarrarDepartment of Pharmacy, College of Pharmacy, Al-Zaytoonah University of Jordan, PO Box 130, Amman 11733, JordanTel +9626795930283Email yazun.jarrar@zuj.edu.joBackground: Testing by pharmacogenomics (PGx) aims to reduce the side-effects of medicines and to optimize therapy.Aim: To ascertain the knowledge and attitudes towards PGx among pharmacy students in Jordan and West Bank of Palestine (WBP).Methods: This cross-sectional study focused on pharmacy students from five universities in Jordan and WBP. Students were asked to answer an online survey comprising 30-closed ended questions measuring the knowledge and attitudes towards PGx.Results: The total number of respondents to the questionnaire was 466. Most (96.1%) respondents knew that genetic variations can affect the drug response. Most students stated that the total number of lectures mentioning PGx was fewer than three. Most (>80%) respondents answered that they knew that human genetics can affect the response, inter-individual variation, and ethnic variations in the drug response. However, their knowledge about US Food and Drug Administration recommendations regarding PGx testing of commonly used drugs was weak. Also, 60.3% of respondents stated that the information they received about PGx was insufficient. Most (>92.7%) students wished to know more about PGx and believed that PGx is helpful in choosing the appropriate drug.Conclusion: Pharmacy students had fair knowledge and good attitudes towards PGx. These factors could aid application of PGx in clinical practice in Jordan and WBP.Keywords: pharmacogenomics, Jordan, West Bank of Palestine, knowledge, pharmacy students